2013
DOI: 10.1093/cvr/cvt190
|View full text |Cite
|
Sign up to set email alerts
|

Early growth response 1 is an early signal inducing Cav3.2 T-type calcium channels during cardiac hypertrophy

Abstract: Cav3.2 is induced early by Egr1 during cardiac hypertrophy and Cav3.2 is an important mediator of Egr1 in regulating cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The hallmarks of pathologic changes of DCM include cardiomyocyte hypertrophy and cardiac fibrosis (20). Current evidence suggests that Smad3, GATA4 and EGR1 are the critical factors in regulating cardiomyocyte hypertrophy and cardiac fibrosis (41)(42)(43)(44)(45)(46)). An array of cardiac genes, including atrial natriuretic peptide, brain natriuretic peptide, α-myosin heavy chain and β-myosin heavy chain, are regulated by GATA4 in response to hypertrophic agonists (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hallmarks of pathologic changes of DCM include cardiomyocyte hypertrophy and cardiac fibrosis (20). Current evidence suggests that Smad3, GATA4 and EGR1 are the critical factors in regulating cardiomyocyte hypertrophy and cardiac fibrosis (41)(42)(43)(44)(45)(46)). An array of cardiac genes, including atrial natriuretic peptide, brain natriuretic peptide, α-myosin heavy chain and β-myosin heavy chain, are regulated by GATA4 in response to hypertrophic agonists (42).…”
Section: Discussionmentioning
confidence: 99%
“…Isoproterenol and phenylephrine infusion-induced cardiac hypertrophy and fibrosis were alleviated by EGR1 deficiency in mice (45). Hsu et al demonstrated that phenylephrine-induced neonatal rat ventricular myocyte and H9c2 cell hypertrophy was prevented by EGR1 knockdown via regulating Ca v 3.2 expression (43). Similarly, Smad3 knockout mice displayed attenuated cardiac remodeling in response to angiotensin II stimulation (46).…”
Section: Discussionmentioning
confidence: 99%
“…Although activation and deactivation of T-type Ca 2ϩ channel gene expression has been observed in many pathological conditions and under various stimuli (4, 26, 35), transcription factors involved in such gene regulation are just beginning to emerge. For instance, repressor element-1 silencing transcription factor, also known as neuron-restrictive silencer factor (15,36), early growth response factor-1 (ERG1) (12), transcription factor GATA4 (28), cardiac homeobox transcription factor Csx/Nkx2.5 (38), and LEF1/␤-catenin complex (39) have been reported to function as a transcriptional regulator of ␣ 1H . However, it is of note that, among these identified transcription factors, ERG1, GATA4, NKX2.5, as well as ␤-catenin signaling have been reported to be regulated by hypoxia (13,25,28,41).…”
Section: Discussionmentioning
confidence: 99%
“…(Harraz et al, 2015) T-type calcium channel activity has also been linked to gene transcription. Activation of T-type channels has been shown to activate nuclear factor of activated T cells in cartilage tissue (Lin et al, 2014) and during the development of cardiac hypertrophy (Hsu et al, 2013;Huang et al, 2013a). T-type channels have also been linked to activation of CREB in cardiomyocytes in response to aldosterone .…”
Section: B Physiologic Roles Of Ca V 3 Calcium Channelsmentioning
confidence: 99%